Aportes mapuce para pensar el género - María Cristina Valdez (Corpus: Archivos Virtuales de la Alteridad Americana, 2017)
The paper presents the contributions of a Mapuce perspective on gender to the discussions in this field, as an intervention in the debate to which we have been invited. At first it refers to the situated character of these reflections, traversing events of the experience of the author as a woman, Mapuce and migrant. It recognizes the way subordinate terms actually intersect, as opposed to the compartmentalized logic of modern dichotomous thinking and making apparent the domination pattern that supports it. It then presents the Mapuce conception of gender and its contributions, and shows, on the one hand, how an “other” conception of gender requires different epistemological and worldview frameworks that convey a non-antagonistic becoming conception in which being a man or woman are not the only options available; on the other hand, the way in which the coloniality of the concept of gender affected the precolonial Mapuce society with consequences traceable to the present. Finally, it challenges the liberal feminist equality claim opposing it to the Mapuce notions of gender.